Coercive Coercion Rhetoric as a Reason for Criminal Abolition (Analysis of LGBT Group Sexual Activity Deviations) - M. Surya Darma; Rajin Sitepu (Istinbath : Jurnal Hukum, 2024)
Sexual behavior is a deviant behavior, basically an abnormal sexual orientation in general. Sexual orientation itself is a tendency that leads to a sense of attraction, romance, emotional and sexual to men, women, or a combination of both. This deviant sexual behavior is carried out by people who have a deviant sexual orientation, which is then known as the LGBT group (Lesbian, Gay, Bisexual, and Transgender/ Transsexual). This research is Normative Law research; the data in this research is secondary data obtained from library materials using library research as a theoretical basis related to the problem researched by the author. The research results show that, First, there is a correlation between physical or biological disabilities and deviant sexual activity in LGBT people. Second, deviations from the sexual activities of LGBT people due to physical or biological defects must be seen as a reason for the abolition of punishment due to coercive force, as stipulated in Article 48 of the Criminal Code, must be seen as coercive forces because deviations from the sexual activities of LGBT people are carried out by encouragement. from within LGBT people which they cannot avoid, just as an act cannot be avoided due to factors within the perpetrator of the criminal act, the meaning of coercive force which has so far been interpreted as coming from within the perpetrator must be reorganized so that it also includes power. Force that comes from within the maker.